2012
DOI: 10.1364/oe.20.010996
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal decomposition with digital holograms

Abstract: We demonstrate a simple approach, using digital holograms, to perform a complete azimuthal decomposition of an optical field. Importantly, we use a set of basis functions that are not scale dependent so that unlike other methods, no knowledge of the initial field is required for the decomposition. We illustrate the power of the method by decomposing two examples: superpositions of Bessel beams and Hermite-Gaussian beams (off-axis vortex). From the measured decomposition we show reconstruction of the amplitude,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 17 publications
0
54
0
Order By: Relevance
“…We have demonstrated a modal decomposition technique for the extraction of the OAM spectrum of an optical field which requires only an SLM and a lens [28][29][30]. For a superposition of two Bessel beams of azimuthal indices l = +3 and -3, we find that while the global OAM is zero, the local OAM spectrum changes radially across the beam.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated a modal decomposition technique for the extraction of the OAM spectrum of an optical field which requires only an SLM and a lens [28][29][30]. For a superposition of two Bessel beams of azimuthal indices l = +3 and -3, we find that while the global OAM is zero, the local OAM spectrum changes radially across the beam.…”
Section: Resultsmentioning
confidence: 99%
“…The first technique involves a spatial light modulator and a Fourier transforming lens to decompose the OAM spectrum of an optical field [28][29][30]. We implement this technique on symmetric and non-symmetric superpositions of non-diffracting higher-order Bessel beams.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Regarding the measurement of the spatially resolved OAM density, only a single approach based on azimuthal decomposition is currently known. 29,30 Even though this technique has the advantage of being independent of the scale of the beam, it necessitates to scan the beam in radial direction, which makes this approach time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…A modified Mach-Zehnder interferometer can also be described to determine both the angular and radial mode content of scalar optical fields [24] but such systems are known to be sensitive to alignment [24]. Digital holograms are also used to extract the azimuthal modal content of optical fields for the reconstruction of its amplitude, phase and OAM density [25]. Recently it has been demonstrated that two spatial light modulators in conjunction with a lens can be used to convert the OAM state of light to a specified lateral position [26][27][28] so that the azimuthal information may be extracted, while leaving the radial component undefined.…”
Section: Introductionmentioning
confidence: 99%